The effects of non carious cervical lesions - morphology, load type and restoration - on the biomechanical behavior of maxillary premolars: a finite element analysis (Bioscience Journal, 2013)
The aim of the present study was to analyze the effects of different types of non-carious cervical lesions (NCCLs) and their morphologies in premolars, restored (or not) with composite resin, on the application three occlusal loadings. The hypothesis was that differing NCCL morphologies, loading types and restoration with composite resin affect stress distribution patterns. A two-dimensional linear Finite Element Analyses (FEA) simulated a healthy tooth model (H) with dental structures including: dentin, pulp, enamel, periodontal ligament, cortical bone, and trabecular bone. Three NCCL morphological models were examined: Mixed (MI), Sauce (SA) and Wedged-shape (WS). All types of lesions were analyzed with and without restoration. The models were considered homogeneous and elastic. In each model three load types: 100N: vertical load (VL), buccal load (BL) and palatine load (PL) were applied. The Maximum Principal Stress values were analyzed. The quantitative analysis of stress (MPa) was identified at five points of the NCCLs according to the morphology of the lesion type: initial point, superior wall, center of lesion, inferior wall and final point. It was found that NCCLs restored with composite resin exhibited stress distribution patterns similar to the healthy tooth model, independent of morphology and load. The Palatine Load was responsible for providing the highest values of accumulated tensions on the NCCL. The highest values of tensile stress on NCCL areas were found in the models without composite resin restoration, which had received PL. It was concluded that the different NCCL morphologies had little effect on stress distribution patterns. The major factors that affected the biomechanical behavior of premolars presenting NCCL were load type and the presence of composite restoration.